2008
DOI: 10.2478/v10042-008-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of angiotensin receptors AT1 and AT2 in adrenal tumors.

Abstract: Angiotensin II is well known to affect the adrenal cell growth and function. Angiotensin receptors AT1 and AT2 were found to be present in the normal adrenal gland. However, the data on the expression of the angiotensin receptors in the adrenal tumors are very scarce. To overcome this gap, the paraffin sections of the adrenal cortical tumors and of pheochromocytomas from the archival material were immunostained with antibodies raised against AT1 (sc-1173) and AT2 (sc-9040) receptor proteins. In hyperplasia of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…AT1 expression is increased in highly differentiated, but not in poorly differentiated laryngeal cancers [19]. In adrenal tumors, AT1 expression is preserved or even increased in benign adenomas, but decreased in adrenal cancers [20]. The pattern of AT2 immunostaining in prostate cancer samples is identical as that of AT1, namely, the AT2 immunopositivity is enhanced at Gleason 2 grade but similar to the control at higher grades of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…AT1 expression is increased in highly differentiated, but not in poorly differentiated laryngeal cancers [19]. In adrenal tumors, AT1 expression is preserved or even increased in benign adenomas, but decreased in adrenal cancers [20]. The pattern of AT2 immunostaining in prostate cancer samples is identical as that of AT1, namely, the AT2 immunopositivity is enhanced at Gleason 2 grade but similar to the control at higher grades of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…International reports on AT 1 R expression in adrenocortical adenoma reveal different viewpoints. The expression of AT 1 R is normal according to Opocher [8] and Marek [9] , but Nawata [10] and Barbara [11] found AT 1 R expression was much higher in adenoma than in normal adrenal gland. In our study, we compared the expression of AT 1 R within adenoma and tissues adjacent to the tumor of 50 APA patients and 12 normal adrenal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for Angiotensin II, a well-established stimulus of aldosterone secretion (Figure 1, panel E) and cell growth, 41,42 were reported two decades ago. 43,44 Only recently, however, a systematic investigation of human adrenal specimens has shown that type 1 receptors (AT1) are by far the most predominantly receptor in both normal adrenal cortex and APA; AT2 are 10-fold less expressed in the normal adrenal cortex, and even less in APAs.…”
Section: Angiotensin II Type 1 (At1) Receptormentioning
confidence: 94%